Lipophilic toxins occurrence in non-traditional invertebrate vectors from North Atlantic Waters (Azores, Madeira, and Morocco): Update on geographical tendencies and new challenges for monitoring routines. (December 2020) - Silva, Marisa; Rodríguez, Inés; Barreiro, Aldo; Kaufmann, Manfred; Neto, Ana Isabel; Hassouani, Meryem; Sabour, Brahim; Alfonso, Amparo; Botana, Luis M.; Vasconcelos, Vitor
Abstract: In the last decades, due to monitoring programs and strict legislation poisoning incidents occurrence provoked by ingestion of naturally contaminated marine organisms has decreased. However, climate change and anthropogenic interference contributed to the expansion and establishment of toxic alien species to more temperate ecosystems. In this work, the coasts of Madeira, São Miguel islands and the northwestern Moroccan coast were surveyed for four groups of lipophilic toxins (yessotoxins, azaspiracids, pectenotoxins, and spirolides), searching for new vectors and geographical tendencies. Twenty-four species benthic organisms were screened using UHPLC-MS/MS technique. We report 19 new vectors for these toxins, six of them with commercial interest ( P. aspera, P. ordinaria, C. lampas, P. pollicipes, H. tuberculata and P. lividus ). Regarding toxin uptake a south-north gradient was detected. This study contributes to the update of monitoring routines and legislation policies, comprising a wider range of vectors, to better serve consumers and ecosystems preservation. Graphical abstract: Unlabelled Image Highlights: 19 new vectors were detected for the screened toxins in edible and commercial interest species. Monitoring practices regarding lipophilic toxins should comprise a wider range of vectors. Geographical tendencies regarding lipophilic toxins distribution were unravelled.